PENDAMPINGAN BIMBINGAN BELAJAR DAN PEMANFAATAN CANVA DI SMA MAARIF LAWANG MELALUI PROGRAM PENGABDIAN KEPADA MASYARAKAT BERBASIS POTENSI (PMBP) - Trio Ageng Prayitno; Nuril Hidayati; Titik Wijayanti; Firda Setiowati (JPM PAMBUDI, 2023)
Based on an agreement between the PMBP team and SMA Maarif Lawang, it is necessary to carry out community service activities in the form of tutoring assistance and the use of Canva. The service aims to help master the concept of biology material that often appears in OSN questions at the Malang Regency Public and Private High School levels and to help increase student creativity in using Canva to create content and manage social media. The service method consists of four stages: Observation, Planning, Implementation, and Evaluation (OPIE). The place of service is SMA Maarif Lawang, Lawang District, Malang Regency. The service instruments are observation sheets and participant enthusiasm questionnaires. The data analysis technique is descriptive quantitative. The results of the service show that the community service activities really help Maarif Lawang High School to master the concept of biology material that often appears in OSN questions at the Malang Regency Private and State High School levels and increase student creativity in using Canva to create content and manage social media. Community service activities run well and smoothly and are in accordance with the expected achievement targets.